2018
DOI: 10.1111/jfs.12536
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mycotoxins co‐occurrence in Italian dried figs and in dried figs‐based products

Abstract: The possible contamination by aflatoxins (AFs), ochratoxin A (OTA), fumonisin B1 (FB1), fusaric acid (FA), and beauvericin (BEA), was investigated in 55 samples of dried figs and dried figs‐based products purchased from the South Italy (Calabria) market. A total of 41 samples showed contamination by at least one of the mycotoxins investigated. Aflatoxin B1 was found in six samples (0.19 — 8.41 μg/kg) total aflatoxins were found in 13 samples (0.5–17.12 μg/kg), OTA was found in 21 samples ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…All OTAcontaminated figs were found in the low or medium category of fluorescence in 2017, but none of the six figs contained detectable aflatoxin B 1 . The natural occurrence of OTA in dried figs has previously been reported (Heperkan et al 2012;Di Sanzo et al 2018;Senyuva et al 2005;Senyuva and Gilbert 2008). Although OTA is not regulated in the EU in dried figs, a maximum limit of 10 μg/kg applies to dried vine fruit (EC 2006b) and therefore, by extrapolation, levels of OTA from 59 to 11,400 μg/kg are clearly unacceptable, notwithstanding the dilution implicit in application of the appropriate sampling plan (EC 2006a).…”
Section: Mycotoxins and Metabolites Other Than Aflatoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…All OTAcontaminated figs were found in the low or medium category of fluorescence in 2017, but none of the six figs contained detectable aflatoxin B 1 . The natural occurrence of OTA in dried figs has previously been reported (Heperkan et al 2012;Di Sanzo et al 2018;Senyuva et al 2005;Senyuva and Gilbert 2008). Although OTA is not regulated in the EU in dried figs, a maximum limit of 10 μg/kg applies to dried vine fruit (EC 2006b) and therefore, by extrapolation, levels of OTA from 59 to 11,400 μg/kg are clearly unacceptable, notwithstanding the dilution implicit in application of the appropriate sampling plan (EC 2006a).…”
Section: Mycotoxins and Metabolites Other Than Aflatoxinsmentioning
confidence: 99%
“…Beauvericin (BEA) was found in 36% of the 2017 figs but only in 2% of the 2018 figs BEA is one of the so-called emerging Fusarium mycotoxins (Jajic et al 2019) which has been reported predominantly as occurring in cereals and was previously found in dried figs (Di Sanzo et al 2018). As an example of one of the more obscure fungal metabolites, levels of bikaverin were found in 19% of figs from 2017 but in only 3% figs from 2018.…”
Section: Mycotoxins and Metabolites Other Than Aflatoxinsmentioning
confidence: 99%
“…Due to the high toxicity of AFs, exposure to these contaminations could threaten human health. The Committee on Food Additives of Joint FAO/WHO (JECFA) recommends that the presence of mycotoxins in meals be minimized to reduce the potential risk (Di Sanzo et al, 2018). Therefore, in order to control AFs in food products, some regulations were established in many countries; the measurement and monitoring of AFs in food products are crucial (Sebaei et al, 2020).…”
Section: Extract and Cleanup Of Afmentioning
confidence: 99%
“…Fumonisins are mycotoxins produced by members of the fungal genus Fusarium . Fumonisins contamination has been reported in maize and maize‐related products, as well as in other foods, including wheat, coffee, and dried figs . Fumonisins are structurally similar to sphingolipids and fumonisin toxicity is associated with the inhibition of ceramide synthase.…”
Section: Introductionmentioning
confidence: 99%